Suspension of ulipristal acetate for uterine fibroids during ongoing EMA's review of liver injury risk: Unfortunate timing during the Covid-19 pandemic!. (September 2020) - Rozenberg, Serge; Revercez, Perrine; Fastrez, Maxime; Vandromme, Jean; Bucella, Dario
Abstract: Objective: EMA decided that with ulipristal acetate (UPA) treatment for uterine fibroids, should be discontinued due to the associated risk of hepatic failure, We analyzed whether the risk of recurrent symptoms due to fibroids may lead to an increased risk of Covid -19 infection and death, that would exceed the former risk of hepatic failure and transplantation. Study design, size, duration: We used a Markov model to generate probabilities. Participants/materials, setting, methods: There are currently about 36, 250 treated patients in Europe. We estimated bleeding probabilities, while using or discontinuing UPA, which may induce a need of medical or surgical management in symptomatic patients, and increase the risk of acquiring a Covid-19 infection, and die from it. We also estimated the risk of suffering a hepatic failure and hepatic transplantation. Main results and the role of chance: Based on our assumptions, ceasing UPA during a Covid 19 pandemic may be associated with a fatality ratio between 4 and 18, due to the Pandemic, whereas pursuing UPA would be associated with a fatality rate due to the pandemic between 1–2, and an added fatality rate due to hepatic impairment of 1. The added risk of stopping UPA may range between 2 and 15 additional deaths. Our calculations suggest that the decision to stop UPA in the middle of the Covid- 19 pandemic may be untimely, since it may result in an increased risk of Covid-19 infection, due to the recurrence of symptoms and the need for medical and surgical treatment. Wider implications of the findings: A decision, like the one EMA took need to be taken in a wider health context of a population, than simply analyzing its role as regulating agent for medications.